(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Iron deficiency anemia (IDA) remains one of the most prevalent nutritional and hematological disorders worldwide, disproportionately affecting women of reproductive age due to physiological and pathological blood loss. This study provides a comprehensive analysis of the relationship between IDA and common gynecological conditions, including menorrhagia, uterine fibroids, endometriosis, and abnormal uterine bleeding. The pathophysiological mechanisms linking chronic blood loss to iron depletion, impaired erythropoiesis, and systemic dysfunction are examined in detail. Clinical and epidemiological evidence demonstrates that women with gynecological disorders characterized by excessive or prolonged menstrual bleeding are at significantly increased risk of developing moderate to severe anemia. Iron deficiency not only compromises oxygen transport but also adversely affects hormonal balance, ovulatory function, immune competence, and overall reproductive health. According to data from Ministry of Health of the Republic of Uzbekistan and international health agencies, IDA prevalence among reproductive-age women remains high, highlighting the need for integrated diagnostic and therapeutic strategies. The findings emphasize that early detection, targeted treatment of underlying gynecological causes, and appropriate iron supplementation are essential for improving clinical outcomes. This study underscores the importance of interdisciplinary management in reducing morbidity, enhancing fertility, and improving quality of life in affected women.